Composición química y digestibilidad de siete plantas forrajeras en Guatemala - Bressani, Ricardo; Jarquin, Roberto; Gonzaga Elias, Luis (2025)
The chemical composition and percentages of digestible nutrients are given for Molasses grass (Melinis minutiflora), Guatemala grass (Tripsacum laxum), Giant Napier (Pennisetum purpureum rar Napier), Pará (Panicum purpurascens), Zacatón (Panicum Spp), Napier Enano (Pennisetum purpureum) and Hybrid napier (Pennisetum purpureum) of the seven, Napier Enano appeared to have the highest protein content and the highest digestibility.